CASC15-S is a tumor suppressor lncRNA at the 6p22 neuroblastoma susceptibility locus - Russell, Mike R. (Cancer Res, 2015)
Chromosome 6p22 was identified recently as a neuroblastoma susceptibility locus, but its mechanistic contributions to tumorigenesis are as yet undefined. Here we report that the most highly significant single nucleotide polymorphism (SNP) associations reside within CASC15, a long non-coding RNA that we define as a tumor suppressor at 6p22. Low-level expression of a short CASC15 isoform (CASC15-S) associated highly with advanced neuroblastoma and poor patient survival. In human neuroblastoma cells, attenuating CASC15-S increased cellular growth and migratory capacity. Gene expression analysis revealed downregulation of neuroblastoma-specific markers in cells with attenuated CASC15-S, with concomitant increases in cell adhesion and extracellular matrix transcripts. Altogether, our results point to CASC15-S as a mediator of neural growth and differentiation, which impacts neuroblastoma initiation and progression.